Palladium(II)-Catalysed Oxidation of Alkenes - Mann, Sam E.; Benhamou, L.; Sheppard, Tom D. (Synthesis, 2015)
This review provides a summary of recent developments in the palladium(II)-catalysed oxidation of alkenes, focusing largely on reactions which lead to the formation of new carbon–oxygen or carbon–nitrogen bonds. Three classes of reaction are covered: i) oxidations proceeding via allylic C–H bond cleavage and formation of a π-allyl complex; ii) Wacker-type oxidations proceeding via nucleopalladation followed by β-hydride elimination; and iii) 1,2-difunctionalisation of alkenes proceeding via nucleopalladation followed by functionalisation of the resulting σ-alkylpalladium(II) intermediate. The mechanisms are discussed alongside the scope and limitations of each reaction.1 Introduction1.1 Background1.2 Oxidation Pathways1.3 Observation of Reaction Intermediates2 Allylic Oxidation2.1 Background2.2 Allylic Oxygenation2.3 Allylic Amination2.4 Allylic Functionalisation with Other Nucleophiles3 The Wacker Oxidation3.1 Background3.2 Variation of the Co-Oxidant3.3 Direct Oxygen-Coupled Wacker Oxidations3.4 Aldehyde-Selective Wacker Oxidations3.5 Wacker Oxidation of Internal Alkenes3.6 Aza-Wacker Oxidations4 Intermolecular 1,2-Difunctionalisation of Alkenes4.1 Introduction4.2 Oxyhalogenation Reactions4.3 Dioxygenation Reactions4.4 Oxycarbonylation Reactions4.5 Aminohalogenation Reactions4.6 Diamination Reactions4.7 Aminooxygenation Reactions4.8 Aminocarbonylation Reactions5 Summary and Conclusions
Keywords: alkenes; oxidation; palladium; Wacker oxidation; catalysis